Inovação em serviços no Brasil: similaridades e divergências com o setor industrial - Braga, Clara Suzana Cardoso (2015)
In Brazil, the services sector, compared to the industrial segment, has smaller volume of studies aimed at understanding their practices under the applied social studies. It is noteworthy in this way, the need for an increase in studies of service sector, the volume of publications, as well as the need for development of analytical models suited to the Brazilian reality. This study aims to compare variables related to innovation, among innovative companies in the industrial sector and service sector, in Brazil. The research can be framed in the positivist epistemological dimension, descriptive methodology and uses descriptive statistics, Average tests and chi-square test, applied to non-aggregated data of Innovation Research - PINTEC 2011, accessed at the headquarters of the Brazilian Institute of Geography and Statistics - IBGE, in Rio de Janeiro. Test results allow to identify that from 48 variables studied, 21 showed similar behavior among innovative companies in the industrial sector and the service sector, therefore is possible to claim, that differences in innovation between industry and services may have been overstated in previous research. The study also highlight the industrial companies are more likely to carry out innovations in marketing that service sector companies and that the latter is more likely to make breakthroughs in product / service companies in the industrial sector. This research does not identify significant differences between the chances of companies in the service sector and the industrial sector, as to product innovation and / or process. With regard to investment in research and development - R & D, identifies the innovative companies in the service sector , on average, made greater expenditure on internal and external activities of Research and Development that the industrial sector.